2022
DOI: 10.1101/2022.02.25.481918
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mucosal microbiomes and Fusobacterium genomics in Vietnamese colorectal cancer patients

Abstract: Perturbations in the gut microbiome have been linked to the promotion and prognosis of colorectal cancer (CRC), with the colonic overabundance of Fusobacterium nucleatum shown as the most consistent marker. Despite the increasing health burden inflicted by CRC in low- and middle-income countries like Vietnam, the CRC-specific microbiome in these populations remains underexplored. Here we conducted a study in Vietnam to enrol 43 CRC patients (cases) and 25 patients with non-cancerous colorectal polyps (controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 108 publications
(116 reference statements)
0
5
0
Order By: Relevance
“… 37 Using international data, indicating that typically around 2.5% of adult asthmatics have ABPA, we estimated 74,658 cases per year. 22 , 38 , 39 Assuming that fungal sensitisation occurs in 33% of the worst 10% adult asthmatics, SAFS was anticipated to affect 98,549 cases annually (102.4/100,000). 22 , 40 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 37 Using international data, indicating that typically around 2.5% of adult asthmatics have ABPA, we estimated 74,658 cases per year. 22 , 38 , 39 Assuming that fungal sensitisation occurs in 33% of the worst 10% adult asthmatics, SAFS was anticipated to affect 98,549 cases annually (102.4/100,000). 22 , 40 …”
Section: Resultsmentioning
confidence: 99%
“… 22 , 38 , 39 Assuming that fungal sensitisation occurs in 33% of the worst 10% adult asthmatics, SAFS was anticipated to affect 98,549 cases annually (102.4/100,000). 22 , 40 …”
Section: Resultsmentioning
confidence: 99%
“…A 2016 Cochrane systematic review of 1337 participants (with 469 deaths) diagnosed with TBM from nine trials concluded that corticosteroids in combination with ATT reduced deaths by nearly one quarter (risk ratio = 0.75, 95% confidence interval = 0.65 to 0.87; highquality evidence) in the short term; however, no difference was found in the rate of disabling neurological deficits [75]. However, in a long-term follow-up study, dexamethasone did not improve the 5-year mortality rate in patients with severe TBM [76]. Corticosteroids reduce meningeal inflammation and cerebral edema, as well as restore vascular permeability [4,75].…”
Section: Corticosteroidsmentioning
confidence: 99%
“…Transferring from saliva to the lower GI tract, the species diversity and abundance of F. nucleatum gradually dropped, indicating they resisted the selective stomach pressure ( Richardson et al., 2020 ). Several F. nucleatum subspecies ( nucleatum, animalis, vincentii, polymorphum ) and potential new subspecies are isolated from the intestine of colorectal cancer patients, and the major encoding virulence factors for F. uncleatum showed evidence of horizontal gene transfer ( Tran et al., 2022 ). Furthermore, intraperitoneal injection successfully established colonization of F. nucleatum in CRC tissue, which suggested the translocation of F. nucleatum through hematogenous route ( Abed et al., 2020 ).…”
Section: Mechanisms Of Oral Microbiome Affecting Intestinal Microbiotamentioning
confidence: 99%